PENGARUH KOMPETENSI DAN KARAKTERISTIK PEKERJAAN TERHADAP KOMITMEN ORGANISASIONAL PERAWAT DENGAN MEDIASI KEPUASAN KERJA - Dimyati, Moh. (Students Journal of Accounting and Banking, 2012)
This study is aimed to determine know the influence and the Job Characteristics to the Nursing Organizational Commitment with the Job Satisfaction Mediation (Pati Ex Residence study Pati regency). Based on preliminary observation to the nursing organizational commitment in Pati Health Departement, there are many problems such as the employees tendency nurse either in Pati Health Departement or in Public Health Center as UPT are less optimal in working, they work to run after the physical project target according to the request of top level government, less attention in activity which is aneeds of local community. This study is done conducted to the nurses in Pati ex-residence who become PNS as many as 102 people by using the cencus taking all population to be samples in research. The stastical technic : used is validity test with the matrix component, reability test with the cronbach alpha, double regression analysis. The T-test, the r2 test with R-square adjusted. The study result known that the competency has a significant influence to the nursing job satisfaction in Pati ex-residence (sig = 0,021). The job characteristics has a signficant positive influence to the nursing job satisfaction in Pati ex-residence (sig = 0,000). Competence significant positive effect on commitment organizational nurses in Ex Pati (sig = 0.000). The job characteristics has a significant positive influence to the nursing organizational commitment in Pati ex-residence (sig = 0,007). The job satisfaction has a significant positive influence to the nursing orgaizational commitment in Pati ex-residence (sig = 0,000). The job satisfaction the competence to the nursing commitment in Pati ex-residence with the job satisfaction mediation. The job satisfaction mediates the job characteristics to the nursing organizational commitment in Pati ex-residence with the job mediation. Keywords: Competence, job characteristic, job satisfaction and organizational commitment